Genetic ability and seedling drought characterization of winter wheat lines in Croatia : Genetska sposobnost i karakterizacija otpornosti na sušu klijanaca linija ozime pšenice u Hrvatskoj - Španić, Valentina (Array, 2022)
Wheat is one of the most common and important cereals in Croatia. Therefore, high selection pressure at wheat breeding program is continually placed on disease, drought and lodging resistance, heading date and end-use quality. The aim of the current study was to evaluate the wheat grain productivity and quality, as well as response of wheat seedlings to drought. Five lines of winter wheat with reference variety Kraljica were used for evaluation of desired traits. In general, investigated wheat lines had such good characters as early maturity, high yield, they were smaller in test weight and protein content, but with higher sedimentation value, dough energy and extensibility, compared to reference variety. Overall, lines Osk.4.330/6-18, Osk.3.530/59-18, Osk.4.354/12-18 out yielded the reference variety with regard to the grain yield. According to the results collected in this research, wheat lines differences in germination energy and seedling growth affected by drought were obtained. All lines could offer farmers tolerance to mild drought during sowing and will achieve high yields. Nevertheless, stability and drought tolerance of investigated winter wheat lines in different environments have to be checked in multi-location trials.